ASUHAN KEBIDANAN PADA BAYI NY. N DENGAN BAYI BERATLAHIR RENDAH DI PUSKESMAS SERANG KOTA TAHUN 2019 - Nuria Fitri Adista; sri Agustin (Poltekkes 'Aisyiyah Banten, 2019)
Neonates are newborns up to the age of 28 days. At that time there was a very big change from life in the womb and there was a maturation in the uterus and organ maturation occurred in almost all systems. The purpose of this study is to be able to perform midwifery care for newborns with low birth weight according to the standardization of midwifery services at Serang Kota Health Center. This research uses descriptive research using primary data through history, physical examination, laboratory examination, and the MCH book. After the assessment, the result is that the baby Ny. N had LBW affected by age <20 years, nutritional status and socioeconomic factors. Therefore, the researchers gave measures in the form of central care by wrapping using sterile gauze, injecting 1 Kg of vit K, and 1% eye ointment, keeping the baby warm, putting the baby in warm ups, observing once every 1 hour, giving ASI every 3 hours and collaboration with doctors. It is hoped that this case study can improve the quality of midwifery care services optimally through immediate treatment, especially for infants with LBW